2005
DOI: 10.1016/j.femsle.2005.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of diversenifHandnifH-like DNA into commercial PCR primers

Abstract: False-positive results due to DNA contamination in PCR reagents have become a big problem in the amplification of small amounts of DNA. Recently, it was revealed that PCR reagents were contaminated with the nifH (dinitrogenase reductase) gene. We found that the PCR primers supplied by some manufacturers contained nifH gene and nifH-like DNA. This contamination resulted in false-positive results when searching for nifH genes in environmental samples. The sequences of the contaminating DNA appeared to be widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Diazotrophs are typically found in low abundance in marine systems, and a nested PCR protocol (455 amplification cycles) is required to amplify the nifH gene. Clone libraries generated using these amplicons may contain heterotrophic nifH sequences amplified from organisms or nucleic acids present in PCR reagents (Kulakov et al, 2002;Zehr et al, 2003a;Goto et al, 2005;Farnelid et al, 2009), high-purity water systems (Matsuda et al, 1996) or sampling equipment. It is insufficient to run negative controls, as amplification of contaminant nifH is sporadic and difficult to reproduce.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diazotrophs are typically found in low abundance in marine systems, and a nested PCR protocol (455 amplification cycles) is required to amplify the nifH gene. Clone libraries generated using these amplicons may contain heterotrophic nifH sequences amplified from organisms or nucleic acids present in PCR reagents (Kulakov et al, 2002;Zehr et al, 2003a;Goto et al, 2005;Farnelid et al, 2009), high-purity water systems (Matsuda et al, 1996) or sampling equipment. It is insufficient to run negative controls, as amplification of contaminant nifH is sporadic and difficult to reproduce.…”
Section: Resultsmentioning
confidence: 99%
“…Although most of these are Cluster I sequences, a Cluster III sequence has been reported (AB198377; Goto et al, 2005). CV9 has 99% nucleotide similarity to a known PCR contaminant, AB198391 (Goto et al, 2005), and is presumed to be a contaminant. Other sequences may be contaminants based on Figure 1 Neighbor-joining tree of partial nifH cyanobacterial sequences obtained from Cape Verde transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…One drawback of the nested PCR approach is the high susceptibility to contamination through handling or presence of nifH genes in PCR reagents (Zehr et al, 2003a;Goto et al, 2005). To circumvent this potential risk, nifH phylotypes may be quantified using QPCR (Hewson et al, 2007).…”
Section: Distribution and Abundances Of Nifh Phylotypes And Transcriptsmentioning
confidence: 99%
“…The efficiency of the real time PCR reactions were 86.8%±0.25, and the specificity of the reactions was confirmed by gel electrophoresis where all samples produced the predicted 361 bp PCR fragment (data not shown). Finally, water was used instead of templates as a negative control to exclude that primers and PCR buffers used in this study were contaminated with nifH genes, as indicated by a study on commercial PCR primers and polymerases (Goto et al 2005). Samples were analysed in three separate runs, with two replicates of each sample in each run.…”
Section: Primer Selectionmentioning
confidence: 99%